Civil Society as the Fifth Estate: Civil Society, Media Reform and Democracy in Korea - Kwak, Ki-Sung (Television, Regulation and Civil Society in Asia, 2002)
Since the Korean War (1950-53), South Korea (hereafter Korea) has undergone a series of political changes. The move towards democratisation was largely spurred on by the demonstrations and riots occurring throughout the 1980s. In 1987 massive demonstrations forced the then President Chun DooHwan to call a new presidential election, and President-elect Rho Tae-Woo to implement more social reforms. The notion of civil society in Korea has been a relatively new concept until very recently, mainly because it has not achieved wide recognition from the public, media or the state. The development of a people’s movement advocating democracy could be said to be the foundation of ‘civil society’ in Korea.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Sliding Back the Screens: Civil Society and the Erosion of Bureaucratic Control of Television in Japan - Hirano, Chalinee (Television, Regulation and Civil Society in Asia, 2002)
Japan in the 1990s differs vastly from what it had been two or three decades earlier. The Japanese state has undergone such a fundamental change that it has been described as a ‘regime shift’ (Pempel 1998). Although the longterm ruling conservative Liberal Democratic Party (LDP) has returned to power after its defeat in 1993, it no longer has an absolute majority in the Cabinet. Surrounded by numerous scandals and corruption charges, both the government and bureaucracy have undergone major reforms to increase transparency and reduce bureaucratic influence over the policy-making process. The Japanese Diet has, for example, passed the Information Disclosure Law to increase openness in the administration. Economic policies have also been transformed to cope with the malaise characterised by continuing problems of bad loans in the financial sector, rising unemployment and declining manufacturing productivity.
Num Pages: 9
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Japon (corpus analysé); _Nettoyé

Television in the Formation of Civil Society: The Role of a Non- Controversial Public Space in Hong Kong - Lee, Paul S. N. (Television, Regulation and Civil Society in Asia, 2002)
Television first appeared in Hong Kong in 1957. It was a cable television service run by the Rediffusion Company which had operated a highly successful wired sound broadcasting service since 1949. Hong Kong was the first British colony to have television. But the Rediffusion television service was very expensive. Its monthly subscription fee was HK$55. In 1958, a technical worker’s monthly wages were HK$360 and an unskilled worker earned only HK$75 (Hong Kong Government 1959: 32). A year before the introduction of free-to-air television in 1967, Rediffusion television had only 67,000 subscribers (Hong Kong Government 1967: 206). Thus before 1967 television was an elite medium and its social impact was minimal.
Num Pages: 8
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Civil Society, Regulatory Space and Cultural Authority in China’s Television Industry - Keane, Michael (Television, Regulation and Civil Society in Asia, 2002)
The question of why civil society presents such appeal for commentators, scholars and journalists writing about developing nations is an important one. The most likely explanation is that a kind of global faith exists in civil society as the driving force of a new world order. This global transformation, exemplified by the collapse of the Soviet bloc, celebrates people’s freedom to participate in public discourse, and ultimately in processes of directly electing political representatives. In this sense the concepts of civil society and the public sphere come together to describe a global anti-authoritarian groundswell where the power of ideas is linked to global cultural development.
Num Pages: 5
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Num Pages: 1
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Civil Society in Charge?: Television and the Public Sphere in Indonesia after Reformasi - Kitley, Philip (Television, Regulation and Civil Society in Asia, 2002)
Television was introduced to Indonesia in 1962 as part of President Sukarno’s flurry of nationalistic ‘symbol wielding’ associated with the Fourth Asian Games (Feith 1963). Televisi Republik Indonesia’s (TVRI) legal status as a creature of the president was reinforced further in Presidential Decree #27, 1963, when it was absorbed after the Games into the ‘Spirit of Sukarno Foundation’, a highly personalised institution under the direct control of the President. TVRI was established as a Foundation in its own right on 20 October 1963, with the President as General Manager (Presidential Decree #215, 1963). Article 3 nominates TVRI as the sole organisation authorised to establish and develop television stations in Indonesia, a highly significant provision which made the commercial broadcasters established in the 1990s dependent on TVRI. TVRI’s status as an activity of the TVRI Foundation was not formally revoked until the enactment of Broadcasting Law #24, 1997, although in administrative practice it came under the control of the Department of Information in 1966.
Num Pages: 10
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Indonésie (corpus analysé); _Nettoyé

Changing Contexts, New Texts: ‘‘Inserting’’ TV into the Transforming Text of Post-1980 Bengali Cinema - Gooptu, Sharmistha (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter analyses a profound transformation of Bengali regional-languagecinema since the early 1980s, a transformation that fundamentally changedthe industry and one that can arguably be attributed at least partly to thecreation of a Bengali television-watching public in the same period. Itfocuses on a trend that emerged in mainstream Bengali cinema during the1980s and was sustained thereafter, and brought into prominence a newconfiguration of elements previously marginal to Bengali films. This trans-formation was to do with mainstream Bengali cinema’s increasing adaptation of what are commonly known as the ‘‘masala’’ or ‘‘formula’’ elementsof Bombay cinema such as racy dialogues, stereotypical villainous char-acters, stylized fights and song-and-dance sequences. This new genre, whichhas commonly been discredited as the Bengali film industry’s totally unim-aginative imitation of the popular Hindi-language cinema of Bombay,completely altered what had been the dominant aesthetic of Bengali cinematill about the mid-1970s. Until this point, Bengali cinema was marked by itsclose relationship with Bengali literature and a Bengali middle-class worldview, greater realism than Bombay cinema or other mainstream regionalcinemas, and naturalistic acting styles, and was radically transformed by agrowing adoption of the ‘‘formula’’ elements commonly identified withpopular Hindi cinema. Industry sources, however, indicate that this newtrend was successful in boosting the Bengali film industry, which had beenswamped by a severe economic crisis since the 1970s. The industry’s crisiswas caused by a host of factors: the most important of these was the Ben-gali middle-class audience’s shift to television as a result of an increasingly unsatisfactory film-going experience in this period. The creation of a Ben-gali television public in the early 1980s shifted audiences from the cinematheatres, thereby significantly reducing film revenues in Calcutta, until then the prime market for Bengali films.
Num Pages: 11
Keywords: 1-Cinéma; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Soaps, Serials and the CPI(M), Crickets Beat Them All: Cricket and Television in Contemporary India - Majumdar, Boria (Television in India: Satellites, Politics and Cultural Change, 2008)
The changing relationship between cricket and satellite television in thecontext of the Indian sub-continent has been a subject of considerablescholarly inquiry. That one nourishes the other is well known. However,what is relatively little known is the degree to which this interdependence hasgrown in recent times. So much so that cricket tournaments, or ratherdesignated TV tournaments, are being planned with alacrity by the Board ofControl for Cricket in India (BCCI). Television rights for these overseastournaments/matches spread over the next 4 years had initially generated $219.5 million for the BCCI.1 On the other hand, satellite channels too havestarted planning cricket programming around these tournaments, program-ming expected to generate millions in advertising revenue.2 While theorganization of such big-money events well encapsulates the symbiotic rela-tionship between cricket and satellite television within a burgeoning Indianeconomy, other local/regional dimensions of this relationship are often noless fascinating. Tele-visual hype generated on the occasion of a regionalcricket body election in July 2006 in West Bengal, especially by the multiple 24-hour Bengali news channels, drew attention to the local variant of thestory involving big-money television and even bigger-money sport. Thischapter, on the basis of two distinct case studies – the implications of the tri-nation 1-day series played in Malaysia in September 2006 involving Aus-tralia, West Indies and India, and Television coverage of the Cricket Asso-ciation of Bengal Elections in July 2006 – will comment on the complex andever-changing relationship between cricket and television in India. At thesame time it will attempt to question the rationale behind this growing interdependence and probe what this means for the Indian nation at large.
Num Pages: 16
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

‘Give Me a Vote, and I Will Give You a TV Set’: Television in Tamil Nadu Politics - Ranganathan, Maya (Television in India: Satellites, Politics and Cultural Change, 2008)
The role of television in democratic politics has been a subject of politicalcommunication studies at least since John F. Kennedy’s performance ontelevised debates supposedly turned around his electoral fortunes and wonhim the 1960 US presidential election. In India too, the potential of themedium in political communication has mostly been analysed in the contextof how television coverage of political leaders and parties, or the lack of it,affects voting behaviour. This chapter differs in its approach. In analysing television’s role in electoral politics in the southern Indian state of Tamil Nadu, it does not look at discourses prevalent on television. Instead, itunderscores how the medium itself has become a part of political discourse,particularly during elections. It points out how television acquired centre-stage as an electoral issue in the 2006 Tamil Nadu assembly elections, evengoing to the extent of dictating poll alliances. Tamil Nadu offers an inter-esting case study to understand the interface between television and Indianpolitics not only because Tamil films and state politics have been inex-tricably intertwined for decades, but also because the two notable political parties in the state have a stake in the private satellite television business.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Num Pages: 30
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

The Mahatma didn’t like the movies and why it matters: Indian broadcasting policy, 1920s–1990s - Jeffrey, Robin (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter examines the ideological and structural foundations of Indianbroadcasting policy as it developed from the 1930s to the 1990s. The chapter argues that the failure of Indian governments to make the most of radioand television for economic and social development stemmed from threesources: (i) the restrictive policies inherited from a colonial state, (ii) thepuritanism of the Gandhian national movement, and (iii) the fear, madevivid by the 1947 partition, of inflaming social conflict. The policies andinstitutions established in the 1940s and 1950s shaped Indian broadcasting for the next 40 years and have been significantly subverted only since 1992as a result of the transformation effected by satellite television.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Television in Post-Reform China: Serial Dramas, Confucian Leadership and the Global Television Market - Zhu, Ying (Routledge, 2008)
This book explores the political, economic, and cultural forces, locally and globally that have shaped the evolution of Chinese primetime television dramas, and the way that these dramas in turn have actively engaged in the major intellectual and policy debates concerning the path, steps, and speed of China’s economic and political modernization during the post-Deng Xiaoping era. It intertwines the evolution of Chinese television drama particularly with the ascendance of the Chinese New Left that favors a recentralization of state authority and an alternative path towards China’s modernization and China’s current administration’s call for building a "harmonious society." Two types of serial drama are highlighted in this regard, the politically provocative dynasty drama and the culturally ambiguous domestic drama. The book also provides cross-cultural comparisons that parallel the textual and institutional strategies of transnational Chinese language TV dramas with dramas from the three leading centers of transnational television production, the US, Brazil and Mexico in Latin America, and the Korean-led East Asia region. The comparison reveals creative connections while it also explores how the emergence of a Chinese cultural-linguistic market, together with other cultural-linguistic markets, complicates the power dynamics of global cultural flows.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Culture, Politics, and Television in Hong Kong - Ma, Eric Kit-wai (Routledge, 1999)
Ma looks at the ways in which the identity of Hong Kong citizens has changed in the 1990s especially since the handover to China in 1997. This is the first analysis which focuses on the role, in this process, of popular media in general and television in particular. The author specifically analyses at the relationship between television ideologies and cultural identities and explores the role of television in the process of identity formation and maintenance.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

The Television of Intervention: Mediating Patron–Client Ties in the Philippines - Corpus Ong, Jonathan (Television Histories in Asia: Issues and Contexts, 2015)
Similar to the other countries discussed in this volume, elite dominance over mass media has been a main characteristic of Filipino history. Foreign-educated Filipino intellectuals from wealthy families founded the early periodicals that demanded reform and/or independence from Spanish colonization in the late nineteenth century (Anderson 1983 ). Today, ‘old rich’ landowning families own and operate television networks, radio stations, and newspapers not only as part of prestigious and profi table media conglomerates, but also in connection with their interests in industries as varied as oil and agriculture to insurance, shipping, and mining.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Philippines (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Unpacking Multiculturalism and Islam in Malaysia: State–Corporate Television Celebrations of Bangsa Malaysia - Khattab, Umi (Television Histories in Asia: Issues and Contexts, 2015)
This chapter presents a critical analysis of media and change in postcolonial Malaysia, a South-East Asian nation of 29 million multicultural people, with a focus on the role of television in the nation’s transformation following independence from British rule in 1957. Despite having inherited the basic democratic institutions of the British political tradition, Malaysia continues to debate the transition from soft authoritarianism to democracy (Means 1996 : 103). Since 1957, Malaysia has been led by a single political party, the Barisan Nasional (BN). While the BN is a coalition of three major ethnic-based political groups, the United Malays National Organisation (UMNO), Malaysian Chinese Association (MCA) and the Malaysian Indian Congress (MIC), it is, in effect, a symbol of Malay-Muslim supremacy (Ketuanan Melayu). UMNO, the dominant group within the party, has, since its formation, aspired to uphold Malay culture as national culture and Islam as the offi cial religion for the country. From the fi rst general elections in 1959 until the 2008 general elections, the BN held two-thirds of the 222 seats in the Dewan Rakyat (House of Representatives). Malaysian media scholar Karthigesu ( 1987 , 1994 ) contends this was largely due to the role of public television, which was launched and promoted by government itself, broadcasting in its colonial service model. In fact, the arrival of state television in 1963 coincided with the formation of the Federation of Malaysia (Moten and Mokhtar 2013 ). In this chapter I argue that television has been pivotal in shaping and transforming the political and cultural landscape of Malaysia as the medium evolved from a strictly national to a loosely global and then fluidly trans-local orientation. While television fi rst enabled the BN to hold its two-thirds majority and build the nation premised on Malay supremacy policies, it subsequently played a part in weakening the BN’s grip over the multiethnic electorate as the UMNO Ketuanan Melayu ideology, layered deep beneath the powdered face of television, surfaced in the digital media era.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Malaisie (corpus analysé); _Nettoyé

Battling Angels and Golden Orange Blossoms: Thai Television and/as the Popular Public Sphere - Farmer, Brett (Television Histories in Asia: Issues and Contexts, 2015)
On 19 September 2006, the fi rst indication many people in Thailand received that the country was undergoing another military coup d’ é tat, the eighteenth such putsch since 1932, was when the nation’s six free-to-air television networks suddenly suspended regular programming and, channel by channel, started to broadcast a generic mix of royal news and light entertainment (Connors and Hewison 2008). Final confi rmation came again via television later that evening in the form of an offi cial announcement, broadcast at regular intervals across all stations from a central feed, in which the armed commanders in chief behind the coup – the awkwardly titled ‘Administrative Reform Group under the Democratic System with the King as the Head of State’ – explained apologetically that they had temporarily taken control of the nation’s airwaves, as indeed of the nation, exhorting viewers to remain calm and reassuring them that normalcy would soon be restored, at which point broadcasting reverted to the same steady flow of innocuous entertainment programming. For all its exceptional gravity, the 2006 coup’s strategic blend of direct state interventionist control of broadcasting combined with a more indirect use of escapist entertainment as populist pacifi er is arguably a structural characteristic of Thai television history writ large.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Thaïlande (corpus analysé); _Nettoyé

Watching Television in Bhutan - Avieson, Bunty (Television Histories in Asia: Issues and Contexts, 2015)
The kingdom of Bhutan drew the international spotlight in 1999 when it became the last nation on earth to introduce broadcast television. It was a deliberate and strategic move by a country that for centuries had chosen to isolate itself from the rest of the world, turning inward to nurture its own culture. The small Himalayan country, whose population in 2013 was estimated at just 733,000, 1 sits uneasily between two feisty behemoths – China and India – each with over a billion people and an ongoing history of border disputes. Bhutan has long been wary of being swamped, either politically or culturally, by these larger neighbours, as well as the world beyond (Penjore 2004 ).
Num Pages: 16
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Bhoutan (corpus analysé); _Nettoyé

Television, Scale and Place-Identity in the PRC: Provincial, National and Global Influences from 1958 to 2013 - Sun, Wanning; Gorfinkel, Lauren (Television Histories in Asia: Issues and Contexts, 2015)
One may argue that Chinese television has already received more than its fair share of attention in the study of Chinese media. As compared with radio and cinema, which developed in the socialist era (1949-78), television has been seen as the dominant medium in the decades of marketization and economic reforms since the late 1970s (Zhu and Berry 2008 ). Television has been studied as a metonym for the ongoing tension and complicity between the Chinese state and the market (e.g., Zhao 1998 ; 2008a) and as a metaphor for the contradictions between a legacy of socialist rhetoric and ethos and a neoliberal market agenda. It is precisely these contradictions that make up what is often referred to as the ‘Chinese characteristics’ (Zhao 2008a; Sun and Zhao 2009 ) of China’s television culture.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Reality Television and the Making of Mobile Publics: The Case of Indian Idol - Punathambekar, Aswin (The Politics of Reality Television: Global Perspectives, 2010)
In the summer of 2007, media coverage of Indian Idol-3 focused attention on how people in the Northeast Indian state of Meghalaya cast aside decades-old separatist identities to mobilize support for Amit Paul, a ﬁnalist from the region. While some fans set up websites and blogs to generate interest and support from the rest of the country and abroad, others formed a fan club and facilitated eﬀorts by a range of groups and organizations to sponsor and manage PCOs (public call oﬃces) in diﬀerent parts of Meghalaya, distribute pre-paid mobile phone cards, and set up landline voting booths. Recognizing the ways in which these activities were beginning to transcend long-standing ethnic, religious, linguistic, and spatial boundaries, state legislators and other politicians soon joined the eﬀort to garner votes for Amit Paul, with the chief minister D. D. Lapang declaring Amit Paul to be Meghalaya’s “brand Ambassador for peace, communal harmony and excellence.”1 It seemed that this three-month-long campaign around a reality television program could set the stage for a remarkable refashioning of the socio-cultural and political terrain in Meghalaya. As one commentator remarked:When Meghalaya’s history is written, it could well be divided into two distinct phases – one before the third Indian Idol contest and one after it. A deep tribal-non-tribal divide, punctuated by killings, riots, and attempts at ethnic cleansing, would mark the ﬁrst phase. A return to harmony and to the cosmopolitan ethos of the past would signify the second. The agent of change: Amit Paul, the ﬁnalist of the musical talent hunt on a TV channel.
Num Pages: 21
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Tears, Talk, and Play: A Window to Gender and Sexuality on Tamil Television - Vangal, Uma (Channeling Cultures: Television Studies from India, 2014)
Tamil television lends itself to some interesting initiatives in gender empowerment through its programming in 3 categories – fiction, reality, and talent shows. This chapter provides a glimpse into television programmes on leading Tamil channels over the last decade (2000–10) from a gender perspective. Focusing particularly on women and transgender characters/hosts, emotional and psychological quotients of the shows and their audiences, moments of dramatic intensity, the chapter demonstrates how the vernacular televisual representations were quite different from the stereotypical portrayals of the mainstream ‘national’ television, even though the programmes were produced, televised, and received within the broader patriarchal framework of Tamil cultural and political contexts. The chapter, as a whole, intends to look at the production, representation and identification of Tamil television soaps and reality shows as vehicle for spotlighting gender issues and alternative sexualities in the public domain.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

When Live News was Too Dangerous: The Early History of Satellite TV in India - Mehta, Nalin (Channeling Cultures: Television Studies from India, 2014)
A unique confluence of technological, political and economic factors in the 1990s drove the transformative process that led to the battering down of the government’s monopoly over television. By the end of the 1990s, the growing strength of Indian capitalism after the liberalization of the Indian economy and the forces of what Thomas Friedman has called ‘Globalisation 3.0’ allowed Indian entrepreneurs to level the playing field. The Indian state, having embarked on economic liberalization, was forced to adapt to satellite television as an agent of global capitalism it certainly did not give up control over television easily or voluntarily. Operating at the junction of public culture, capitalism and globalization, satellite news networks have had profound implications for the state, politics, democracy and identity formation. Despite all their shortcomings and sensationalism, the emergence of satellite television news networks has enhanced and strengthened deliberative Indian democracy.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television News and an Indian Infotainment Sphere - Thussu, Daya Kishan (Channeling Cultures: Television Studies from India, 2014)
The exponential growth of television news in India – from one state controlled network until 1991 to more than 100 news channels in 2012 – has transformed broadcast journalism in the country. This proliferation of news networks has intensified competition for audience and advertising revenue, leading to excessive marketization of news, which increasingly veers toward infotainment. The chapter examines the challenges faced by Indian television news – focusing on economic and political dimensions of television news - and its implications for the world’s largest democracy.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

TV after Television Studies: Recasting Questions of Audiovisual Form - Roy, Abhijit (Channeling Cultures: Television Studies from India, 2014)
This chapter locates India, and broadly the post-colonial context, within the larger debates concerning television’s audiovisual form and mode of address. It tries to demonstrate that certain key traits in Indian popular performative traditions, representing an ‘alternative’ negotiation with modernity, are somewhat homologous with what western theorists have tried to specify (though in contradicting terms) as the features of televisual mode of address and ‘flow’. The chapter reads the specific imports of this correspondence in histories of Indian television with special reference to a somewhat novel way television has started imagining the nation after liberalization. The significance of the Indian popular film form as lending a major legacy to tele-viewership in India constitutes a major strand of argument.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Num Pages: 16
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television in Post-Reform Vietnam: Nation, Media, Market - Nguyen-Thu, Giang (Routledge, 2018)
This book explores Vietnamese popular television in the post-Reform era, that is, from 1986, focussing on the relationship between television and national imagination. It locates Vietnamese television in the experiences of everyday life and the prevailing network of power relations resulting from marketization and globalization, and, as such, moves beyond the clichéd assumption of Vietnamese media as a mere propagandist instrument of the party state. With examples from a wide range of television genres, the book demonstrates how Vietnamese television enables novel conditions of cultural oppression as well as political engagement in the name of the nation. In sharp contrast to the previous image of Vietnam as a war-torn land, post-Reform television conjures into being a new sense of national belonging based on an implicit rejection of the socialist past, hopes for peace and prosperity, and anxieties about a globalized future. This book highlights the richness of Vietnam’s current culture and identity, characterized, the book argues, by ‘fraternity without uniformity’.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Australie (lieu de production du savoir); Vietnam (corpus analysé); _Nettoyé

The Little Emperors’ New Toys: A Critical Inquiry into Children and Television in China - Zhao, Bin (Springer, 2013)
Drawing on original research I conducted in the late 1980s, the book argues for a critical approach to the study of children and television. It begins with critical reappraisals of previous empiricist and interpretative studies to set the ground for a different theoretical inquiry which links biography with history. The situated activity of children's television viewing therefore has to be related to the broader historical and cultural formations in post-Mao China. By way of a methodological pluralism of questionnaire survey, in-depth interviews and observation, the book provides the reader with a thorough critical analysis of the rise of the new commercial ethic in Chinese society in general, and in the sector of media and communications in particular, at the very historical turning point of the late 1980s. Soon after that, Deng Xiaoping made his significant tour to south China, reckoning a big step forward towards further liberalization and started to form a brave new world in China ever since.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Television in Bangladesh: News and Audiences - Roy, Ratan Kumar (Routledge India, 2020)
This book examines the role of 24/7 television news channels in Bangladesh. By using a multi-sited ethnography of television news media, it showcases the socio-political undercurrents of media practices and the everydayness of TV news in Bangladesh. It discusses a wide gamut of issues such as news making; localised public sphere; audience reaction and viewing culture; impact of rumours and fake news; socio-political conditions; protest mobilization; newsroom politics and perspectives from the ground. An important intervention in the subject, this book will be useful to scholars and researchers of media studies, journalism and mass communication, anthropology, cultural studies, political sociology, political science, sociology, South Asian studies, as well as television professionals, journalists, civil society activists, and those interested in the study of Bangladesh.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Bangladesh (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Producing Domestic Abuse in Pakistani Television: Between Commerce, Ratings and Social Responsibility - Cheema, Munira (Television for Women, 2016)
Before the liberalisation of television in 2000, Pakistan had one terrestrial channel.The Pakistan Television Corporation (commonly known as PTV) had been the statebroadcaster since 1964 and thus PTV content reflected the policies of differentgovernments. Liberal governments relaxed control over gender on screen – womencould be seen without dupatta – while religiously inclined governments brought intheir own agendas with restrictions on appearance of women, such as the dupattapolicy (see, for example, Ali, 1986; Suleman, 1990; Kothari, 2005; Nasir, 2012).1 In2002, the Independent Media Corporation launched its channel Geo News fromPakistan, followed by other networks, marking the formal launch of the policy ofliberalisation of media on television. Presently, five media groups have control of thePakistani media industry, including electronic and print media. These are Inde-pendent Media Corporation, Pakistan Herald Publications, ARY Group, WaqtGroup and Lakson Group (see for example Proffitt and Rasul, 2013). The broad-casting industry in Pakistan follows an advertiser-driven model that is run through asystem of ratings. At the time of the fieldwork reported here (October-April 2011),Media Logic and Gallup were the two operators that determined the popular tastesof consumers through ratings.2
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); _Nettoyé

Defining the Nation?: Lebanese Television and Political Elites (1990–2005) - Nötzold, Katharina (Frank & Timme, 2013)
Katharina Nötzold explores whether and how mass media can contribute to nation-building after civil war. Drawing on the example of Lebanon’s audiovisual media organisations, which are mostly privately owned by politicians, she demonstrates how political elites use television to transmit their visions of post-war society. Lebanon’s nation-building process from 1990 to 2005 was characterized by Syrian dominance over political life. From an extensive content analysis of Lebanese news and interviews with analysts, journalists and managers from all Lebanese TV stations, it emerges that political information on television focused more on divisive experiences than cohesive ones. This has underpinned continued sectarianism in Lebanon, in the media as in society at large, and has impeded nation-building. Biographische Informationen Katharina Nötzold is a political scientist and RCUK Research Fellow at the University of Westminster's Arab Media Centre, and she completed her PhD in Media and Communications at the University of Erfurt, Germany. She lived in Beirut and Amman and worked previously for the Center for International Peace Operations, Berlin. She is editor of Westminster Papers in Communication and Culture and author of articles on Arab media and media representations of migrants and Islam. Reihe Medien und politische Kommunikation – Naher Osten und islamische Welt - Band 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Allemagne (lieu de production du savoir); Liban (corpus analysé); _Nettoyé

Making of Exile Culture: Iranian Television in Los Angeles - Naficy, Hamid (University of Minnesota Press, 1993)
Naficy explores the seemingly contradictory way in which immigrant media and cultural productions serve as the source both of resistance and opposition to the domination by host and home country's social values while simultaneously serving as vehicles for personal and cultural transformation and assimilation of those values.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; Iran (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

China Turned On: Television, Reform and Resistance - Lull, James (Taylor & Francis Group, 2013)
The years following the Cultural Revolution saw the arrival of television as part of China's effort to 'modernize' and open up to the West. Endorsed by the Deng Xiaoping regime as a 'bridge' between government and the people, television became at once the official mouthpiece of the Communist Party and the most popular form of entertainment for Chinese people living in the cities. But the authorities failed to realize the unmatched cultural power of television to inspire resistance to official ideologies, expectations, and lifestyles. The presence of television in the homes of the urban Chinese strikingly broadened the cultural and political awareness of its audience and provoked the people to imagine better ways of living as individuals, families, and as a nation. Originally published in 1991, set within the framework of China's political and economic environment in the modernization period, this insightful analysis is based on ethnographic data collected in China before and after the Tiananmen Square disaster. From interviews with leading Chinese television executives and nearly one hundred families in Beijing, Shanghai, Guangzhou, and Xian, the author outlays how Chinese television fosters opposition to the government through the work routines of media professionals, television imagery, and the role of critical, active audience members.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Broadcasting Politics in Japan: NHK and Television News - Krauss, Ellis S. (Cornell University Press, 2018)
The aftermath of Japan's 1945 military defeat left its public institutions in a state of deep crisis; virtually every major source of state legitimacy was seriously damaged or wholly remade by the postwar occupation. Between 1960 and 1990, however, these institutions renewed their strength, taking on legitimacy that erased virtually all traces of their postwar instability.How did this transformation come about? This is the question Ellis S. Krauss ponders in Broadcasting Politics in Japan; his answer focuses on the role played by the Japanese mass media and in particular by Japan's national broadcaster, NHK. Since the 1960s, television has been a fixture of the Japanese household, and NHK's TV news has until very recently been the dominant, and most trusted, source of political information for the Japanese citizen. NHK's news style is distinctive among the broadcasting systems of industrialized countries; it emphasizes facts over interpretation and gives unusual priority to coverage of the national bureaucracy. Krauss argues that this approach is not simply a reflection of Japanese culture, but a result of the organization and processes of NHK and their relationship with the state. These factors had profound consequences for the state's postwar re-legitimization, while the commercial networks' recent challenge to NHK has helped engender the wave of cynicism currently faced by the state. Krauss guides the reader through the complex interactions among politics, media organizations, and Japanese journalism to demonstrate how NHK television news became a shaper of Japan's political world, rather than simply a lens through which to view it.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Visual Political Communication in Popular Chinese Television Series - Schneider, Florian; Dudbridge, Glen; Pieke, Frank N. (BRILL, 2012)
In Visual Political Communication in Popular Chinese Television Series, Florian Schneider analyses political discourses in Chinese TV dramas, the most popular entertainment format in China today.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); Chine (corpus analysé); Pays-Bas (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); _Nettoyé

Politics After Television: Hindu Nationalism and the Reshaping of the Public in India - Rajagopal, Arvind (Cambridge University Press, 2001)
In January 1987, the Indian state-run television began broadcasting a Hindu epic in serial form, The Ramayana, to nationwide audiences, violating a decades-old taboo on religious partisanship. What resulted was the largest political campaign in post-independence times, around the symbol of Lord Ram, led by Hindu nationalists. The complexion of Indian politics was irrevocably changed thereafter. In this book, Arvind Rajagopal analyses this extraordinary series of events. While audiences may have thought they were harking back to an epic golden age, Hindu nationalist leaders were embracing the prospects of neoliberalism and globalisation. Television was the device that hinged these movements together, symbolising the new possibilities of politics, at once more inclusive and authoritarian. Simultaneously, this study examines how the larger historical context was woven into and changed the character of Hindu nationalism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Nation, and Culture in Indonesia - Kitley, Philip (Ohio University Press, 2014)
The culture of television in Indonesia began with its establishment in 1962 as a public broadcasting service. From that time, through the deregulation of television broadcasting in 1990 and the establishment of commercial channels, television can be understood, Philip Kitley argues, as a part of the New Order’s national culture project, designed to legitimate an idealized Indonesian national cultural identity. But Professor Kitley suggests that it also has become a site for the contestation of elements of the New Order’s cultural policies. Based on his studies, he further speculates on the increasingly significant role that television is destined to play as a site of cultural and political struggle.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Indonésie (corpus analysé); _Nettoyé

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé